Learn to be happy—an experimental study in clinical context with depressive patients in Germany - Sequeira-Nazaré, Elena Renée; Schmitz, Bernhard (Frontiers in Psychology, 2024)
The increase in the number of people with mental disorders and the relapse rate of depressive patients give reason to constantly question and further develop psychotherapeutic interventions in order to stabilize therapy effects. Studies show that the art of living, described as the ability to lead a conscious and reflective life, can be learned and trained. The question arises as to what role the development of “art of living skills” have played in the treatment of depressed patients to date, and to what extent the targeted promotion of art of living within the framework of the therapy of depressed patients has an effect on the well-being and the level of depression that goes beyond this. The study is based on a mixed design. Study participants in the first experimental group (EG1, n = 53) each received one session of 50 min psychotherapy per week for 4 weeks. The second experimental group (EG2, n = 54) received psychotherapy equivalent to EG1 with additional life-skills reflection questions, which were to be answered every day and recorded in a diary. The control group (n = 53) received neither therapy nor reflection questions. The art of living, degree of depression, and satisfaction with life were assessed before and after the 4-week therapy and in the follow-up after 3 months, and the effects were compared. There was a significant decrease in the depression score over the 4 weeks in both therapy groups. EG2 showed a greater decrease in depression over the 4 weeks. However, the difference did not persist over the 3 months. Furthermore, in EG2 there was a significant increase in the Art of Living, Satisfaction with life, and Flourishing Scale over the 4 weeks, while in EG1 there was no change. However, the comparison in the follow-up after 3 months also shows that these effects could not stabilize. Overall, the results provide promising indications for integrating the art of living as a concept more strongly into the therapy of depressive patients. The question arises as to what long-term effects result from additional life skills stimulation and how the therapy effects gained can be stabilized over a longer period of time.